The 24-month metabolic benefits of the healthy living partnerships to prevent diabetes: A community-based translational study. Issue 3 (May 2018) - Pedley, Carolyn F.; Case, L. Douglas; Blackwell, Caroline S.; Katula, Jeffrey A.; Vitolins, Mara Z.
Abstract: Aims: Large-scale clinical trials and translational studies have demonstrated that weight loss achieved through diet and physical activity reduced the development of diabetes in overweight individuals with prediabetes. These interventions also reduced the occurrence of metabolic syndrome and risk factors linked to other chronic conditions including obesity-driven cancers and cardiovascular disease. The Healthy Living Partnerships to Prevent Diabetes (HELP PD) was a clinical trial in which participants were randomized to receive a community-based lifestyle intervention translated from the Diabetes Prevention Program (DPP) or an enhanced usual care condition. The objective of this study is to compare the 12 and 24 month prevalence of metabolic syndrome in the two treatment arms of HELP PD. Materials and methods: The intervention involved a group-based, behavioral weight-loss program led by community health workers monitored by personnel from a local diabetes education program. The enhanced usual care condition included dietary counseling and written materials. Results: HELP PD included 301 overweight or obese participants (BMI 25–39.9 kg/m 2 ) with elevated fasting glucose levels (95–125 mg/dl). At 12 and 24 months of follow-up there were significant improvements in individual components of the metabolic syndrome: fasting blood glucose, waist circumference, HDL, triglycerides and blood pressure and the occurrence of the metabolic syndrome in the intervention group compared to the usual care group. Conclusions: This study demonstrates that a community diabetes prevention program in participants with prediabetes results in metabolic benefits and a reduction in the occurrence of the metabolic syndrome in the intervention group compared to the enhanced usual care group.